Measurement of food safety culture using survey and maturity profiling tools. (August 2016) - Jespersen, Lone; Griffiths, Mansel; Maclaurin, Tanya; Chapman, Benjamin; Wallace, Carol A.
Abstract: Organizational culture is defined by dimensions and characteristics that can be used to measure food safety culture in food manufacturing through a food safety maturity model. Maturity models from quality, health care, and information technology have been used since early 1970 and this work presents a novel food safety culture maturity model with five capability areas and food safety pinpointed behaviours specific to functions and levels in a food manufacturing company. A survey tool linked to the model is used to measure a company's position within the maturity model framework. The method was tested with a Canadian food manufacturer and proved valuable to measure food safety culture across the five capability areas, which provides the manufacturer with a map for prioritizing future efforts to strengthen food safety culture. Highlights: Theory of organizational culture was applied to measure food safety culture characteristics. Food safety culture was measured using a self-assessment survey with pinpointed food safety behaviours. A maturity model was developed to measure food safety culture in food manufacturing. The tool was tested with a Canadian food manufacturer resulting in a measure of the organization's food safety culture across six capability areas.